99mTc-labeled monosaccharide kits: development methods and quality control; Scientific Reports; Vol. 10 - Stasyuk (Stasiuk) E. S. Elena Sergeyevna; Skuridin V. S. Viktor Sergeyevich; Rogov A. S. Alexander Sergeyevich; Zelchan R. V. Roman Vladimirovich; Sadkin V. L. Vladimir Leonidovich; Varlamova N. V. Natalya Valeryevna; Nesterov E. A. Evgeny Alexandrovich (2020, 2020)
Title screen